Cloning of a cDNA encoding bovine erythropoietin and analysis of its transcription in selected tissues - Suliman, H.B.; Majiwa, Phelix A.O.; Feldman, B.F.; Mertens, B.; Logan-Henfrey, L.L. (Elsevier, 1996)
A bobine cDNA encoding erythropoietin (Epo) was isolated by polymerase chain reaction (PCR) amplification and screening of a bovine kidney cDNA library. The sequenced cDNA has a length of 1312 bp and an open reading frame that encodes a predicted 192-amino-acid (aa) protein, including a putative signal sequence of 25 aa. A mature protein of 167 aa (18.4 kDa) results upon cleavage of the putative signal peptide. The deduced bovine mature Epo peptide exhibits 96, 88, 83, 82 and 79 sequence identity to that of sheep, swine, human, monkey and rat, respectively. The expression of the bovine Epo gene in tissues from a severely anemic calf, bovine fetus and a healthy steer was analysed by a competitive RT-PCR method. In kidneys of the severely anemic calf, Epo mRNA levels increased 60-fold relative to that from the kidneys of the healthy steer. Epo mRNA levels were threefold higher in the liver of the bovine fetus than that in its kidneys. Low levels of Epo transcripts were detected in RNA from spleen of the severely anemic calf and the bovine fetus. No Epo transcripts were detectable in spleen from the healthy steer.